Conservation of transcriptional activation functions of the NF-kappa B p50 and p65 subunits in mammalian cells and Saccharomyces cerevisiae. - Moore, P A (1993)
The NF-kappa B transcription factor complex is composed of a 50-kDa (p50) and a 65-kDa (p65) subunit. Both subunits bind to similar DNA motifs and elicit transcriptional activation as either homo- or heterodimers. By using chimeric proteins that contain the DNA binding domain of the yeast transcriptional activator GAL4 and subdomains of p65, three distinct transcriptional activation domains were identified. One domain was localized to a region of 42 amino acids containing a potential leucin zipper structure, consistent with earlier reports. Two other domains, both acidic and rich in prolines, were also identified. Of perhaps more significance, the same minimal activation domains that were functional in mammalian cells were also functional in the yeast Saccharomyces cerevisiae. Coexpression of the NF-kappa B inhibitory molecule, I kappa B, reduced the transcriptional activity of p65 significantly, suggesting the ability of I kappa B to function in a similar manner in S. cerevisiae. Surprisingly, while the conserved rel homology domain of p65 demonstrated no transcriptional activity in either mammalian cells or S. cerevisiae, the corresponding domain in p50 was a strong transcriptional activator in S. cerevisiae. The observation that similar domains elicit transcriptional activation in mammalian cells and S. cerevisiae demonstrates strong conservation of the transcriptional machinery required for NF-kappa B function and provides a powerful genetic system to study the transcriptional mechanisms of these proteins.